Impact of lockdown during the COVID-19 outbreak on multi-scale air quality. (1st June 2021) - Bray, Casey D.; Nahas, Alberth; Battye, William H.; Aneja, Viney P.
Abstract: One of the multi-facet impacts of lockdowns during the unprecedented COVID-19 pandemic was restricted economic and transport activities. This has resulted in the reduction of air pollution concentrations observed globally. This study is aimed at examining the concentration changes in air pollutants (i.e., carbon monoxide (CO), nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), ozone (O3 ), and particulate matters (PM2.5 and PM10 ) during the period March–April 2020. Data from both satellite observations (for NO2 ) and ground-based measurements (for all other pollutants) were utilized to analyze the changes when compared against the same months between 2015 and 2019. Globally, space borne NO2 column observations observed by satellite (OMI on Aura) were reduced by approximately 9.19% and 9.57%, in March and April 2020, respectively because of public health measures enforced to contain the coronavirus disease outbreak (COVID-19). On a regional scale and after accounting for the effects of meteorological variability, most monitoring sites in Europe, USA, China, and India showed declines in CO, NO2, SO2, PM2.5, and PM10 concentrations during the period of analysis. An increase in O3 concentrations occurred during the same period. Meanwhile, four major cities case studies i.e. in New York City (USA), Milan (Italy), Wuhan (China), and New Delhi (India) have also shown a similar reduction trends as observed on the regional scale, and an increase in ozone concentration. This study highlights that the reductions in air pollutant concentrations have overall improved global air quality likely driven in part by economic slowdowns resulting from the global pandemic. Highlights: Global NO2 column observations were reduced by approximately 9.19% (March) and 9.57% (April) due to COVID 19 lockdown. Most monitoring sites in Europe, USA, China, and India showed declines in pollutant concentrations during analysis. Four major cities case studies also shown a similar reduction trends and an increase in ozone concentration.